Alzheimer's disease risk variants modulate endophenotypes in mild cognitive impairment. Issue 8 (24th February 2016) - Louwersheimer, Eva; Wolfsgruber, Steffen; Espinosa, Ana; Lacour, André; Heilmann‐Heimbach, Stefanie; Alegret, Montserrat; Hernández, Isabel; Rosende‐Roca, Maitée; Tárraga, Lluís; Boada, Mercè; Kornhuber, Johannes; Peters, Oliver; et al.
Abstract: Introduction: We evaluated the effect of Alzheimer's disease (AD) susceptibility loci on endophenotypes closely related with AD pathology in patients with mild cognitive impairment (MCI). Methods: We selected 1730 MCI patients from four independent data sets. Weighted polygenic risk scores (PGS) were constructed of 18 non‐apolipoprotein E ( APOE ) AD risk variants. In addition, we determined APOE genotype. AD endophenotypes were cognitive decline over time and cerebrospinal fluid (CSF) biomarkers (aβ, tau, ptau). Results: PGS was modestly associated with cognitive decline over time, as measured by mini‐mental state examination (MMSE) (β ± SE:−0.24 ± 0.10; P = .012), and with CSF levels of tau and ptau (tau: 1.38 ± 0.36, P = 1.21 × 10 −4 ; ptau: 1.40 ± 0.36, P = 1.02 × 10 −4 ). Discussion: In MCI, we observed a joint effect of AD susceptibility loci on nonamyloid endophenotypes, suggesting a link of these genetic loci with neuronal degeneration in general rather than with Alzheimer‐related amyloid deposition.